Pengaruh Socmed Usage, Cultural Intelligence Terhadap Kinerja Umkm Dengan Mediator Entrepreneurial Orientation - Felix Florentino O. S. , F.X. Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to determine the impact of social media usage and cultural intelligence on SME performance with entrepreneurial orientation as an intervening variable on SME around Java Island. The sampling method used in this study using purposive sampling method and was obtained 94 respondents as samples using questioner. Data processing techniques using partial least square analysis helped with SmartPLS 3.3.2 and SPSS ver. 21. The results obtained in this research are social media usage and cultural intelligence have a significant positive effect on SME performance, while entrepreneurial orientation partially mediated the effect of social media usage and cultural intelligence on SME performance. The implication of this study is the need to understand the role of social media usage, cultural intelligence, entrepreneurial orientation will increase SME performance.